2013
DOI: 10.1002/adma.201300445
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene Foams Cross‐linked with Pre‐encapsulated Fe3O4 Nanospheres for Enhanced Lithium Storage

Abstract: Electrostatic assembly between Fe3O4 nanospheres and graphene oxide, and subsequent hydrothermal assembly with additional graphene sheets, leads to Fe3O4 nanospheres encapsulated in the graphene shells and interconnected by the graphene networks. Such 3D Fe3O4 /graphene foams exhibit enhanced lithium storage with excellent cycling performance and rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
491
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(508 citation statements)
references
References 50 publications
17
491
0
Order By: Relevance
“…Owing to these outstanding properties, graphene sheets have been widely applied in different fields such as lithium ion batteries [6][7][8][9], supercapacitors [10][11][12], biomedical materials [13][14][15], and composite materials [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these outstanding properties, graphene sheets have been widely applied in different fields such as lithium ion batteries [6][7][8][9], supercapacitors [10][11][12], biomedical materials [13][14][15], and composite materials [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [21] demonstrated that the compressive failure strength and the toughness of APTS monoliths improved by 19.9 and 92%, respectively, when 0.1 wt% functionalized GO sheets were added. In general, nanofillers are directly dispersed in a resin matrix via thermal exfoliation at high temperature [35][36][37][38] or are dispersed in an organic solvent which is later evaporated [9,[39][40][41], resulting in polymer composites. However, Yang et al [42] recently described a new economically viable method where GO was dispersed through a two-phase extraction resulting in GO/epoxy resin composites.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the progression of the previously developed hybrids, improved specifi c capacity values were reported through the exploitation of 3D graphene matrixes incorporating, for example, SnO 2 , [252][253][254] Fe 3 O 4 , [ 255,256 ] MoS 2 , [ 257,258 ] SnS 2 , [ 259 ] MnO, [ 260 ] TiO 2 [ 261 ] or Si [ 262 ] particles. Indeed, the graphene network appeared to be benefi cial for reducing the material resistance and to improve the mechanical stability of the electrode.…”
mentioning
confidence: 99%
“…To further improve the rate performance of MOs, much effort has been made to accommodate the active materials with porous conductive scaffolds to form the nanocomposites such as carbon nanotubes [11][12][13][14][15][16][17][18][19], graphene [20][21][22][23][24] and carbon nanofibers [25][26][27][28][29] because they could provide long-range conductivity, well controlled interface between MOs and conducting carbons, and more robust network structure. In particular, CNTs is a good candidate for a support matrix in novel anode material for enhanced lithium storage due to its high electrical conductivity, rich porosity and high tensile strength [30,31].…”
Section: Australiamentioning
confidence: 99%